Willingness of rural communities to reforest with native tree species in central Chile. Issue 6 (10th September 2019) - Smith‐Ramírez, Cecilia; Castillo, Jessica; Armesto, Juan J.
Abstract : Economic development of rural people is not always feasible along with concomitant forest restoration, especially when meager reforestation incentives are oriented to poor rural people who probably are not willing to plant native species in their small plots of land. Forest restoration incentives have been created by the Chilean government to engage poor rural people in reforestation using native tree species to recover degraded lands. Our objective was to compare the willingness of people from rural communities to plant native species if they had to bear the costs or if the government did, and we related the answers to environmental and socioeconomic variables. Of the 217 respondents 53.9% were interested in planting native trees if subsidies became available. Interest decreased if the respondents had to pay for the cost, but only slightly. The willingness to reforest was significantly greater at lower distance from the community to the nearest native forest for those with lower income level, and was higher when there was use of nontimber forest products or wood by the respondents. However, in spite of the positive disposition to plant native trees, only 23% of the respondents were interested in planting on their own land, which is a requirement to receive the economic incentives. Most respondents were willing to plant in open sites and on degraded hillsides that surround their communities. We conclude that despite monetary incentives, benefits cannot reach most rural inhabitants because of their lack of interest in reforesting their own land.